Effect of lactation on serum total cholesterol & triglyceride - Begum, Khadiza; Begum, Rokeya; Akhter, Qazi Shamima; Sultana, Nusrat; Bari, Shamima (Bangladesh Journal of Physiology and Pharmacology, 2014)
Background: There is an association between breast feeding & maternal lipid profile. Pregnancy related hyperlipidaemia reverse quickly with lactation. Objective: To observe Serum Total cholesterol & triglyceride in lactating & nonlactating mother. Method: The present cross sectional study was conducted in the Department of Physiology, Dhaka Medical College, Dhaka, during the period of July 2010 to June 2011. A total 300 subjects were included within the age limit from 20 to 40 years of women. Among them100 were normal healthy subjects & had child above 3 years were considered as group A (control). The rest 200 women were selected as study subject (group B) having child between the age 6 weeks to 2 years. Group B is again subdivided into group B1 (100 lactating mother) & group B2 (100 nonlactating mother). The subjects were selected from pediatric ward & OPD of pediatrics, DMCH and BSMMU, Dhaka. Data were collected in data collection sheet after taking informed written consent of the subjects. The study parameters total cholesterol & Triglyceride were done in the Department of Physiology, Dhaka Medical College. The data were analyzed by computer with SPSS programs using unpaired Student ?t test. Results: In group B1 total cholesterol & triglyceride levels were non significantly higher than that of group A but in group B2 these values were significantly higher than that of group A. Within the study groups all these values were significantly higher in nonlactating mother than lactating mother. It was observed that high level of study parameters were more in B2 than that of group B1. Conclusion: From the results of the present study it may be concluded that lactation has effect on lowering serum total cholesterol & triglyceride which may preferably related to health education for the mother. http://dx.doi.org/10.3329/bjpp.v29i1-2.20060 Bangladesh J Physiol Pharmacol 2013; 29(1&2) : 1-7